Social Identity of Football Supporter’s Given (Phenomenology Study to Supporter of Pasoepati in Indonesia) - Suryo Putro, Waskito Aji (Universitas Negeri Medan, 2017)
Abstract:Pasoepati is a group of supporter that supporting to the Persis Football Club of Solo. Pasoepati is a phenomenon group which is really complex. Marginally, the social identity of Pasoepati, as a group or a community, makes them different with other groups of supporters in Indonesia. Pasoepati appeared in 2000s century in the hard social context because of the existence of gangs in that time. And finally, Pasoepati capable to get a kind of sympathy of people in Solo and Indonesia, as the supporter which is has politeness and sportive, in conveying a support. Pasoepati appears in political and cultural context of supporter institution, but once Pasoepati answers it by a group that has a cultural basic without institution.Furthermore, this study is aim to know the construction of Pasoepati social identity in appearance of history context. Besides that, this study aim to know how Pasoepati represents the sportive support in football. This study applies qualitative method. The approach that used is phenomenology. The researcher knows that getting the comprehensive understanding about Pasoepati, phenomenology is the more appropriate approche. Besides, by applying that approach the researcher tries to describe the data in perspective subject of the study. Therefore, the researcher gets directly participation in the field and tries to as near as possible to the subject of the study.In this study, the researcher uses perspective theory identity. In practicing in the field and presenting the data, the researcher uses phenomenology theories which are established by Mostakas. In which, the fact in the field is presented in the various and qualified way. The result of the study gets some political, economical, social and cultural phenomena, which built the social identity of Pasoepati.And the conclusion is, the researcher understands the representation is done by Pasoepati is good expecially in giving the sportive support. Pasoepati is a group that ready to acculturate the habitual or culture from the outside which is thought well and appropriate to keep the existence. However, Pasoepati still aware that the acculturation is done should still in the line for keeping the identity social that was built. The key words: social identity, supporter, football, sportive, Pasoepati